Radiation refrigeration coating and preparation method thereof

By using modified polyurethane emulsion, mesoporous nanosilica, barium oxide and modified nanosilver in radiation refrigeration coatings, the problems of insufficient radiation refrigeration effect and poor adhesion of existing coatings are solved, and higher refrigeration efficiency, service life and durability are achieved.

CN119505673AInactive Publication Date: 2025-02-25杭州绿冰纳米科技有限公司
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411701121.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The radiation refrigeration effect of existing radiation refrigeration coatings is not obvious and have poor adhesion, which affects its promotion and application.

Method used

Using a radiation refrigeration coating, which includes a first filler and a second filler, the polyurethane emulsion is modified by a silane coupling agent, combined with mesoporous nanosilica, barium oxide and modified nanosilver to improve the bond strength and optical properties of the coating.

Benefits of technology

It improves the service life of the coating, the alternating properties of the cold and heat, and the high-temperature crack resistance, enhances its reflectivity to sunlight and infrared radiation refrigeration, and improves the water resistance, wear resistance and ultraviolet light absorption capacity of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505673A_ABST
    Figure CN119505673A_ABST
Patent Text Reader

Abstract

The invention discloses a radiation refrigeration coating and a preparation method thereof. The radiation refrigeration coating comprises a first filler and a second filler, the mass ratio of the first filler to the second filler is (1-3): (1-5), and the first filler comprises the following components in percentage by weight: 50-70% of a polyurethane emulsion, 10-15% of a silane coupling agent, 8-10% of multi-mesoporous nano-silica and 5-8% of talcum powder; the second filler comprises the following components in percentage by weight: 60%-70% of polyethylene glycol, 10%-15% of a dispersing agent and 5%-8% of nano barium oxide; 5%-8% of tannic acid; 3%-5% of nano silver; the viscosity of the polyurethane emulsion ranges from 300 cps to 800 cps. The radiation refrigeration coating disclosed by the invention has the advantages that a refrigeration film has larger infrared radiation refrigeration capacity in an atmospheric window, better ultraviolet light absorption capacity and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of radiation cooling, and in particular relates to a radiation cooling coating and a preparation method thereof. Background Art

[0002] All objects in nature, as long as their temperature is above absolute zero, constantly transmit heat in the form of electromagnetic waves. The sun radiates heat to the earth mainly in the form of short wavelengths, while long-wave radiation is the main way of heat exchange between the ground and the atmosphere. The temperatures of the ground (300K), atmosphere (250K) and external space (3K) are arranged from high to low. Part of the solar radiation is reflected by the atmosphere and the ground, and part is absorbed by the atmosphere and the ground; at the same time, the ground and the atmosphere also radiate each other, and the atmosphere and external space radiate each other at any time.

[0003] Water vapor, CO2, ozone, etc. in the atmosphere have the ability to strongly absorb and emit long-wave radiation (forming a heat preservation effect), among which the absorption of water vapor is the most obvious. The radiation emitted by water vapor to the ground surface has two strong absorption bands, one in 4.5-8.0 microns and the other in the far infrared region above 18 microns. However, the atmosphere absorbs very little radiation in the 8-13 micron band, which is an important atmospheric transparent window; that is, the earth's atmosphere has very low radiation to the ground in the transparent window band (8-13μm) and high transmission. Therefore, in the long-wavelength heat exchange between the atmosphere and the ground, the radiation from the ground atmospheric transparent window band can directly pass through the atmosphere to transfer heat, forming a radiation cooling effect. It can be seen that radiation cooling is to use the universe as a cold source and the objects on the ground as heat sources to establish a radiation heat transfer channel. Through the "atmospheric transparent window", without consuming energy, the heat of the ground objects is directly transferred to the universe in the form of electromagnetic wave radiation in a specific band, thereby achieving the purpose of cooling.

[0004] There have been public reports on radiant cooling technology, but the solar reflectance and atmospheric window emissivity of coatings obtained by most technologies are low, the cooling effect of the coatings is not obvious, and the coating adhesion is poor, which seriously affects the promotion and application of radiant cooling coatings. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a radiant cooling coating and a preparation method thereof, aiming to solve the technical problems of the existing radiant cooling coating having unclear radiant cooling effect and poor adhesion.

[0006] To achieve the above object, the present invention provides the following technical solution: a radiant cooling coating, comprising a first filler and a second filler, wherein the mass ratio of the first filler to the second filler is (1-3):(1-5), wherein:

[0007] The first filler comprises the following components in terms of weight percentage: 50-70% polyurethane emulsion, 10%-15% silane coupling agent, 8%-10% mesoporous nano-silica, and 5%-8% talc;

[0008] The second filler comprises the following components by weight: 60%-70% polyethylene glycol, 10%-15% dispersant, 5%-8% nano barium oxide, 5%-8% tannic acid, and 3%-5% nano silver;

[0009] The viscosity of the polyurethane emulsion is 300-800 cps.

[0010] Furthermore, the nano-barium oxide is spherical, and the particle size of the nano-barium oxide is 0.5-2 microns; the particle size of the mesoporous nano-silicon dioxide is 3-5 microns.

[0011] Furthermore, the particle size of the nanosilver is 6-8 microns.

[0012] Furthermore, the preparation method of the mesoporous nano-silica comprises:

[0013] Dissolve sodium carbonate and cationic surfactant in deionized water, heat to 80°C, and stir for 1-2 hours to form a mixture A;

[0014] Add silicon source to mixture A, stir for 40 to 70 minutes, wash and dry.

[0015] Furthermore, the silicon source is any one of sodium silicate, diatomaceous earth and tetraethyl orthosilicate.

[0016] Furthermore, the mass ratio of the sodium carbonate, the surfactant and the silicon source is 1:1:6.

[0017] Furthermore, the silane coupling agent is any one of vinyltrimethoxyethoxysilane and trimethoxysilane.

[0018] The present application also discloses a method for preparing the above-mentioned radiation cooling coating, comprising the following steps:

[0019] S01: polyurethane emulsion, silane coupling agent, mesoporous nano-silica, and talc are weighed according to the ratio to form a mixture A;

[0020] S02: polyethylene glycol, dispersant, and nano-barium oxide are weighed according to the ratio to form a mixture B, and the mixture B is added to the mixture A and stirred for 40 minutes to form a mixture C;

[0021] S03: Weighing tannic acid and nano-silver according to the ratio respectively and dispersing them in a liquid dispersant to obtain a dispersion of modified nano-silver particles;

[0022] S04: Evenly mix the mixture C and the modified nano silver particles, add a cross-linking curing agent, and dry to obtain a radiation cooling coating.

[0023] Furthermore, the cross-linking curing agent is any one selected from polycarbodiimide curing agents, polyisocyanate curing agents and epoxy silane curing agents.

[0024] Furthermore, in step S04, the drying temperature is 70-90°C.

[0025] The beneficial effects of the present invention are as follows: compared with the prior art, the radiation cooling coating in the present invention has the following advantages:

[0026] (1) The polyurethane emulsion is modified by a silane coupling agent so that it can be closely bonded to the substrate during the coating process, so that the coating and the substrate have a strong bonding strength, and it is not easy to fall off after long-term use, thereby improving the service life of the coating; by adding talcum powder, the linear expansion coefficient of the coating can be changed, the hot and cold alternating performance of the coating and the anti-cracking performance at high temperature can be improved, and at the same time, the sedimentation of the coating during storage can be slowed down, and the coating can be prevented from sagging, thereby improving the water resistance and wear resistance of the coating;

[0027] (2) Through the unique lattice absorption band of mesoporous nano-silica, the refrigeration film can have a larger infrared radiation cooling capacity at the atmospheric window, and the refractive index is further improved by using barium oxide, and it has better ultraviolet light absorption capacity. The composite particles formed by embedding barium oxide into the skeleton of mesoporous nano-silica can not only make full use of the larger specific surface area of ​​nano-silica, but also the coating obtained by this material has higher mechanical properties;

[0028] (3) The reflectivity of the coating to sunlight can be improved by the mirror effect of nanosilver itself; the nanosilver particles can be half-coated by tannic acid to form a nanoscale core-shell structure; the surface of the nanosilver particles can be modified by grafting tannic acid on the surface of the nanosilver particles, which is convenient for the loading of mesoporous nano-silicon dioxide; the nano-silicon dioxide particles are loaded on the surface of the tannic acid shell layer, which can reduce the rate at which the silver particles release silver ions in the air and increase the service life of the coating; in addition, the modified nanosilver particles and the mesoporous nano-silicon dioxide are connected to each other by covalent bonds and van der Waals forces, and the combination effect is better.

[0029] Other advantages, objectives and features of the present invention will be described in the following description and will be apparent to those skilled in the art to some extent, or those skilled in the art may be taught from the practice of the present invention. The objectives and other advantages of the present invention may be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the present invention provides the following drawings for illustration:

[0031] Figure 1 The present invention is a flow chart of a method for preparing a radiant cooling coating according to an embodiment of the present invention. DETAILED DESCRIPTION

[0032] This embodiment provides a radiation cooling coating, including a first filler and a second filler, wherein the mass ratio of the first filler to the second filler is (1-3):(1-5), wherein:

[0033] The first filler comprises the following components in terms of weight percentage: 50-70% polyurethane emulsion, 10%-15% silane coupling agent, 8%-10% mesoporous nano-silica, and 5%-8% talc;

[0034] The second filler comprises the following components by weight: 60%-70% polyethylene glycol, 10%-15% dispersant, 5%-8% nano barium oxide, 5%-8% tannic acid, and 3%-5% nano silver;

[0035] The viscosity of the polyurethane emulsion is 300-800 cps.

[0036] In the present application, the polyurethane emulsion is modified by a silane coupling agent so that it can be tightly combined with the substrate during the coating formation process, so that the coating and the substrate have a strong bonding strength, and it is not easy to fall off after long-term use, thereby improving the service life of the coating; by adding talcum powder, the linear expansion coefficient of the coating can be changed, the hot and cold alternating performance of the coating and the anti-cracking performance at high temperature can be improved, and at the same time, the sedimentation of the coating during storage can be slowed down, and the coating can be prevented from sagging, and the water resistance and wear resistance of the coating can be improved; through the unique lattice absorption band of multi-mesoporous nano-silica, the refrigeration film can have a larger infrared radiation refrigeration capacity at the atmospheric window, and the refractive index is further improved by using barium oxide, and it has better ultraviolet light absorption capacity. The composite particles formed by embedding barium oxide into the skeleton of mesoporous nano-silicon dioxide can not only make full use of the large specific surface area of ​​nano-silicon dioxide, but also obtain a coating with high mechanical properties through the material; the reflectivity of the coating to sunlight can be improved through the mirror effect of nano-silver itself; the nano-silver particles can be half-coated by tannic acid to form a nano-scale core-shell structure, and the surface of the nano-silver particles can be modified by grafting tannic acid on the surface of the nano-silver particles, which is convenient for the loading of mesoporous nano-silicon dioxide. The nano-silicon dioxide particles are loaded on the surface of the tannic acid shell layer, which can reduce the rate at which the silver particles release silver ions in the air and improve the service life of the coating; in addition, the modified nano-silver particles and the mesoporous nano-silicon dioxide are connected to each other through covalent bonds and van der Waals forces, and the combination effect is better.

[0037] Preferably, the liquid viscosity of the polyurethane may be 300cps, 400cps, 500cps, 600cps, 650cps, 700cps, 800cps, etc. In the present application, the liquid viscosity of the polyurethane is preferably 650cps, which has the best compatibility with the above components and is easy to adjust the hydrophobicity.

[0038] In the present application, the mass ratio of the first filler to the second filler is 1:1, 1:2, 1:3, 1:4, 2:3, 2:4, 3:4, 3:5, etc. Preferably, in the present application, the mass ratio of the first filler to the second filler is 1:1.

[0039] Preferably, the nano-barium oxide is spherical, and the particle size of the nano-barium oxide is 0.5-2 microns; the particle size of the multi-mesoporous nano-silicon dioxide is 3-5 microns. In this way, since the particle size of the nano-barium oxide is smaller than the particle size of the nano-silicon dioxide, the nano-barium oxide can be embedded in the skeleton of the multi-mesoporous nano-silicon dioxide, and the formed composite particles can make the refrigeration film have a larger infrared radiation cooling capacity at the atmospheric window and have better ultraviolet light absorption capacity. Specifically, the particle size of the nano-barium oxide is 0.5 microns, 0.8 microns, 1.0 microns, 1.2 microns, 1.4 microns, 1.8 microns, 2.0 microns; the particle size of the multi-mesoporous nano-silicon dioxide is 3 microns, 3.5 microns, 4.0 microns, 4.5 microns, 4.7 microns, 5 microns, etc.

[0040] Furthermore, the particle size of the nanosilver is 6-8 microns. Specifically, the particle size of the nanosilver can be 6 microns, 6.5 microns, 7 microns, 7.5 microns, 8 microns, etc. The particle size of the nanosilver is larger than the particle size of the mesoporous nanosilicon dioxide; on the one hand, the nanosilver is prevented from being embedded in the mesoporous nanosilicon dioxide; on the other hand, the nanosilver with a larger particle size is semi-coated with tannic acid to form a larger nanoscale core-shell structure, providing a larger specific surface area for the loading of the mesoporous nanosilicon dioxide.

[0041] Furthermore, the preparation method of the mesoporous nano-silica comprises:

[0042] Dissolve sodium carbonate and cationic surfactant in deionized water, heat to 80°C, and stir for 1-2 hours to form a mixture A;

[0043] Add silicon source to mixture A, stir for 40 to 70 minutes, wash and dry.

[0044] In the present application, a cationic surfactant is used as a template and the temperature of the reaction system is increased to increase the molecular thermal motion in the reaction system. Under the action of stirring, the cationic surfactant is distributed more evenly in the solution. By adding sodium carbonate, the solution is made alkaline, which can accelerate the hydrolysis rate of the silicon source. The silicon source has a negative charge due to the adsorption of OH- in the solution. The positively charged silicon source formed with the surfactant undergoes a deposition reaction through electrostatic force and van der Waals force, so that the silicon source can be precipitated in the organic network of the surfactant micelles. The two undergo a polymerization reaction and solidify to form a pore wall. The cationic surfactant is washed away by washing and drying, and the remaining part is the mesoporous structure supported by the silicon source material, forming a multi-mesoporous nano-silica.

[0045] Furthermore, the silicon source is any one of sodium silicate, diatomaceous earth and tetraethyl orthosilicate.

[0046] Furthermore, the mass ratio of the sodium carbonate, the surfactant and the silicon source is 1:1:6.

[0047] Furthermore, the silane coupling agent is any one of vinyltrimethoxyethoxysilane and trimethoxysilane.

[0048] Examples 1-7 respectively provide a radiation cooling coating, wherein the mass ratio of the first filler to the second filler is 1:1, and the types and usage amounts of each component in the first filler and the second filler are shown in Table 1.

[0049] Table 1 Proportions of the components in Examples 1-7

[0050]

[0051] See also Figure 1 As shown, the present application also discloses a method for preparing the radiation cooling coating as described above, comprising the following steps:

[0052] S01: polyurethane emulsion, silane coupling agent, mesoporous nano-silica, and talc are weighed according to the ratio to form a mixture A;

[0053] S02: polyethylene glycol, dispersant, and nano-barium oxide are weighed according to the ratio to form a mixture B, and the mixture B is added to the mixture A and stirred for 40 minutes to form a mixture C;

[0054] S03: Weighing tannic acid and nano-silver according to the ratio respectively and dispersing them in a liquid dispersant to obtain a dispersion of modified nano-silver particles;

[0055] S04: Evenly mix the mixture C and the modified nano silver particles, add a cross-linking curing agent, and dry to obtain a radiation cooling coating.

[0056] In the present application, by pre-mixing mixture A and mixture B, nano-barium oxide can be embedded in mesoporous nano-silicon dioxide, so that nano-barium oxide is fixed in the skeleton formed by mesoporous nano-silicon dioxide, so that the refrigeration film has a larger infrared radiation refrigeration capacity at the atmospheric window, and the refractive index is further improved by using barium oxide, and has better ultraviolet light absorption capacity; then, the nano-silver particles can be semi-coated with tannic acid in advance to form a nano-scale core-shell structure, and the surface of the nano-silver particles can be modified by grafting tannic acid on the surface of the nano-silver particles, so as to facilitate the loading of mixture C, and the nano-silicon dioxide particles are loaded on the surface of the tannic acid shell layer, which can reduce the rate at which the silver particles release silver ions in the air and improve the service life of the coating; finally, by adding a cross-linking curing agent and drying, a radiation refrigeration coating can be obtained, so that the prepared coating has better bonding force and enhances the durability of the coating.

[0057] Furthermore, the cross-linking curing agent is any one selected from polycarbodiimide curing agents, polyisocyanate curing agents and epoxy silane curing agents.

[0058] Furthermore, in step S04, the drying temperature is 70-90° C. Specifically, the drying temperature can be 70° C., 80° C., 85° C., 88° C., 90° C., etc., and the appropriate drying temperature can be adjusted according to actual needs.

[0059] The radiative cooling coating prepared in Examples 1-7 was prepared into a thin film and attached to glass for testing. The thermochromic temperature of the thin film prepared above was tested using an ultraviolet spectrophotometer. The optical performance in the 0.3-2.5 μm band was characterized by measuring the reflection spectrum and transmission spectrum of the film using an integrating sphere and silicon and indium gallium arsenide detectors. The optical performance in the 2.5-20 μm band was characterized by measuring the reflection spectrum and transmission spectrum of the film using an integrating sphere Fourier transform spectrometer. The hardness of the film was tested using an LX-A rubber hardness tester. The impact resistance of the film was tested. The test results are shown in Table 2

[0060] Table 2 Performance of thin film coating formed by radiation cooling coating

[0061]

[0062] It can be seen from Table 2 that with the increase of the content of mesoporous nano-silica and barium oxide, the optical properties of the prepared film are significantly enhanced. This may be due to the unique lattice absorption band of mesoporous nano-silica, which can make the refrigeration film have a larger infrared radiation refrigeration capacity in the atmospheric window, and the use of barium oxide and modified nano-silver to further improve the refractive index and reflectivity, and have better ultraviolet light absorption capacity; and it can be seen from Examples 1-7 that the adhesion of the radiation refrigeration coating is roughly consistent, which may be due to the same content ratio of the polyurethane emulsion and the silane coupling agent.

[0063] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A radiant cooling coating, characterized in that: It comprises a first filler and a second filler, wherein the mass ratio of the first filler to the second filler is (1-3):(1-5), wherein: The first filler comprises the following components in terms of weight percentage: 50-70% polyurethane emulsion, 10%-15% silane coupling agent, 8%-10% mesoporous nano-silica, and 5%-8% talc; The second filler comprises the following components by weight: 60%-70% polyethylene glycol, 10%-15% dispersant, 5%-8% nano barium oxide, 5%-8% tannic acid, and 3%-5% nano silver; The viscosity of the polyurethane emulsion is 300-800 cps.

2. The radiant cooling coating according to claim 1, characterized in that: The nano-barium oxide is spherical, and the particle size of the nano-barium oxide is 0.5-2 microns; the particle size of the multi-mesoporous nano-silicon dioxide is 3-5 microns.

3. The radiant cooling coating according to claim 2, characterized in that: The particle size of the nano silver is 6-8 microns.

4. The radiant cooling coating according to claim 3, characterized in that: The preparation method of the mesoporous nano-silica comprises: Dissolve sodium carbonate and cationic surfactant in deionized water, heat to 80°C, and stir for 1-2 hours to form a mixture A; Add silicon source to mixture A, stir for 40 to 70 minutes, wash and dry.

5. The radiant cooling coating according to claim 4, characterized in that: The silicon source is any one of sodium silicate, diatomaceous earth and tetraethyl orthosilicate.

6. The radiant cooling coating according to claim 4, characterized in that: The mass ratio of the sodium carbonate, the surfactant and the silicon source is 1:1:

6.

7. The radiant cooling coating according to claim 1, characterized in that: The silane coupling agent is any one of vinyltrimethoxyethoxysilane and trimethoxysilane.

8. A method for preparing the radiant cooling coating according to any one of claims 1 to 7, characterized in that: The steps include: S01: polyurethane emulsion, silane coupling agent, mesoporous nano-silica, and talc are weighed according to the ratio to form a mixture A; S02: polyethylene glycol, dispersant, and nano-barium oxide are weighed according to the ratio to form a mixture B, and the mixture B is added to the mixture A and stirred for 40 minutes to form a mixture C; S03: Weighing tannic acid and nano-silver according to the ratio respectively and dispersing them in a liquid dispersant to obtain a dispersion of modified nano-silver particles; S04: Evenly mix the mixture C and the modified nano silver particles, add a cross-linking curing agent, and dry to obtain a radiation cooling coating.

9. The method for preparing a radiant cooling coating according to claim 8, characterized in that: The cross-linking curing agent is any one selected from polycarbodiimide curing agents, polyisocyanate curing agents and epoxysilane curing agents.

10. The method for preparing a radiant cooling coating according to claim 8, characterized in that: The drying temperature in step S04 is 70-90°C.

Citation Information

Cited By

  • Radiation refrigeration coating for natural gas bottle and preparation method of radiation refrigeration coating

    CN120059587A

  • A radiation cooling coating for natural gas cylinders and its preparation method

    CN120059587B

  • Inorganic radiation refrigeration coating with zinc tailings-prepared secondary zinc oxide as filler, coating and preparation method of inorganic radiation refrigeration coating

    CN121406166A